PEMBELAJARAN KUBUS DAN BALOK MENURUT STANDAR PENGAJARAN NCTM DENGAN SETTING KOOPERATIF - Elli Kusumawati (Edumatica : Jurnal Pendidikan Matematika, 2011)
Abstract This design should enable the students to improve the creativity, create a challenging and comfortable condition for the students, provide various learning experience, and make the student learn by doing something. The mathematic learning method based on the NCTM teaching standard can be used by the teacher to increase the student’s comprehension. The NCTM teaching standard consists of 4 components, namely (1) giving task, (2) discourse, (3) learning environment, (4) analysis. Based on those standard, the learning process is carried out with cooperative setting. The early step, teacher  explain the learning objectives and explains the learning steps they are going to conduct and form a learning group. The primary step consists of giving task, accomplishing discourse in a group, presentation, and discussion about the group work result, arranging the learning environmental, and analysis of teaching and learning. The final step is the learning analysis in form of opinion on the student’s activity during the learning process and giving final test. The accomplishment of assignment in cooperative study group helps students understand the materials. The given task makes students fell being challenged so that they can dig their intellectual capacity. The arrangement of learning environment done by the teacher will create the classroom atmosphere. Students give a positive respond to this learning method. Student’s states that they enjoy with the learning situation.